Respuesta :
How to get answer: [tex]1. \mathrm{Subtract\:}6\mathrm{\:from\:both\:sides}\\1.5. 6+2\left(x-4\right)-6=12-6\\2. Simplify\\2.5. 2\left(x-4\right)=6\\3. \mathrm{Divide\:both\:sides\:by\:}2\\3.5. \frac{2\left(x-4\right)}{2}=\frac{6}{2}\\\\4.Simplify\\4.5.x-4=3\\5.\mathrm{Add\:}4\mathrm{\:to\:both\:sides}\\5.5. x-4+4=3+4\\6. Simplify\\6.6. x=7[/tex]
First distribute the 2 to the values inside the parentheses.
[tex]6+2(x-4)=12[/tex]
[tex]6+2x-8=12[/tex]
Combine like terms. (6+-8)
[tex]6+-8=-2[/tex]
[tex]-2+2x=12[/tex]
Add 2 on both sides of the equation.
[tex]2+-2+2x=12+2[/tex][tex]2x=14[/tex]
Divide both sides by 2.
[tex]\frac{2x}{2}[/tex]=[tex]\frac{14}{2}[/tex]
[tex]x=7[/tex]
The value of x is equal to 7.